Does ownership matter for the provision of professionalized services? Hip operations at publicly and privately owned clinics in Denmark - Andersen, Lotte Bogh; Jakobsen, Mads (2011)
In terms of clinical procedures (to take the example used in this article, hip operations), both public and private organizations provide highly professionalized services. For this service type, our knowledge about ownership differences is sparse. To begin to fill this gap, we investigate how the ownership of Hip clinics affects professional behaviour, treatement quality and patient satisfaction. The comparison of private and public hip clinics is bassed on dara from the Danish Hip Arthoplasty Register and the Danish Central Patient Register combined with 20 semi-structured interviews. We find that private clinics employ stronger individual financial inventives and try harder to increase the income/cost ratio than do public clinics. Private clinic optimize non-clinical factors such as waiting time much more than public clinics and have fewer complication-prone patients than public clinics. However, the clinical procedures are very similar in the two types of clinics. Private clinics do not achieve bettrer clinical results, but patient satisfaction is nevertheless higher with private clinics. The implication is that ownership matters for highly professionalized services, but professionalism neutralizes some - but not all - ownership differences. - Reproduced.
Keywords: Health Services